Enhanced expression of xylanase in Aspergillus niger enabling a two-step enzymatic pathway for extracting β-glucan from oat bran. (June 2023) - Li, Yangyang; Li, Cen; Muhammad Aqeel, Sahibzada; Wang, Yachan; Zhang, Quan; Ma, Jianing; Zhou, Jingwen; Li, Jianghua; Du, Guocheng; Liu, Song
Graphical abstract: Highlights: Multigene integration in A. niger was achieved using a modified CRISPR-Cas9 system. The xynA activity in A. niger was enhanced 3, 650-fold via a combined strategy. A two-step enzymatic pathway for extracting β-glucan (85.1% purity) was developed. Abstract: The high cost and process complexity limit the enzymatic extraction of β-glucan. In this study, β-glucan was extracted from oat bran in a two-step enzymatic pathway using a recombinant strain of Aspergillus niger AG11 overexpressing the endogenous xylanase (xynA) and amylolytic enzyme. First, co-optimization of promoter and signal peptide and a fusion of glucoamylase (glaA) fragment were integrated into the β-glucosidase ( bgl ) locus to improve xynA expression. Then, the optimized expression cassette was simultaneously integrated into bgl, α-amylase amyA, and acid α-amylase ammA loci, yielding the Rbya with 3, 650-fold and 31.2% increase in xynA and amylolytic enzyme activity than the wild-type strain, respectively. Finally, Rbya's supernatants at 72 h (rich in xynA and amylolytic enzyme) and 10 d (rich in proteases) were used to decompose xylan/starch and proteins in oat bran, respectively, to obtain 85.1% pure β-glucan. Rbya could be a robust candidate for the cost-effective extraction of β-glucan.